(untitled) (Research, Society and Development, 2020)
Objective: To propose recommendations for caregivers and family members when caring for the elderly in the midst of the COVID-19 pandemic. Method: This research is a narrative review with reflective analysis of the current literature. The search for information took place in September and October 2020, in the virtual health library, Scielo electronic library, on the Ministry of Health portal, PAHO, and also from SBGG. Results: In order for care to be possible, caregivers must be in adequate physical, psychological and emotional conditions. Therefore, due to the Covid-19 pandemic, old and new habits need to be established by everyone living with the elderly. Conclusion: COVID-19 has become a major health challenge, especially for the elderly population, it is currently one of the most vulnerable, needing care to be redoubled so that it is possible to safeguard the health of this population, thus, come into focus the role of caregivers, whether formal or informal.